Impact of different judo rules: analysis of scores and penalties in Paris Grand Slam Championship - Guarise Katicips, L. F.; Silva Júnior, J. N.; Lima Kons, R.; Detanico, D. (Revista Internacional de Ciencias del Deporte, 2018)
In the last two decades, the International Judo Federation (IJF) has been implementing a series of changes in its official rules, in order to improve efficiency and achieve more dynamism in judo combat. The aim of the present investigation was to analyze the effects of judo rule changes proposed by IJF in three periods (2011, 2016 and 2017), considering the scores and penalties in the Grand Slam Paris (GSP). The values of the scores (yuko, wazari and ippon) and the penalties (shido) were relativized by the total number of matches. The normality of data was assessed by the Kolmogorov-Smirnov test. Two-way analysis of variance and Bonferroni post hoc test (or t-test when necessary) were used to compare the scores, penalties and the efficiency index among GSP2011, GSP2016 and GSP2017. The significance level was set at p< 0.05.The results indicated that GSP2016 presented higher incidence of penalties in the general male teams and lower number of yuko score compared to the GSP2011 and GSP2017, while the GSP2011 showed higher efficiency in the female teams (general and medalists). Ippon was the score that determined the outcome of the matches in GSP2011 and GSP2017 particularly for male medalist teams. We conclude that the rule changes in the GSP2016 deviated from the IJF objectives compared to GSP2011 and GSP2017, considering the greater importance of scores than punishments.